A Review Of The Job Satisfaction Theory For Special Education Perspective - et. al., Farah Azaliney Binti Mohd Amin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Job satisfaction reflects a positive feeling towards the task performed. Through this value of job satisfaction, an individual will feel confident and enthusiastic in every job undertaken. In the field of education, of course the discussion is focused on the job satisfaction of teachers because the main role in the delivery of knowledge in schools is the teachers. Even in special education specifically, job satisfaction is very important in increasing the accauntibility of special education teachers as well as motivating themselves to continue to dedicate themselves to religion, race and country. The discussion of job satisfaction, has been explained in several theories that can be linked to special education. This study was conducted to examine the previous theories related to teacher job satisfaction which can be referenced by teachers.